Release: CIC Announces Aboriginal Bursary Program - External Relations, University of Regina (External Relations, University of Regina, 2004)
Joint release: Crown Investments Corporation, First Nations University of Canada, University of Regina. Crown Investments Corporation of Saskatchewan (CIC) is providing up to $2 million in bursaries over the next five years for Aboriginal students enrolled in both First Nations University of Canada and the University of Regina. Staff no